Notation-agnostic Subprocess Modeling for Adaptive Case Management - Tenschert, Johannes; Dunzer, Sebastian; Matzner, Martin (Lecture Notes in Information Systems and Organisation, 2021)
Even though knowledge work comprises tasks that cannot be modeled a priori, some structure for routine work or an outlined course of action is often necessary. Knowledge workers perform structured and ad-hoc activities – and a wide range of requirements typically yields many tools. To avoid redundant and scattered process information, a single system of record capable of consolidating flexibility and modeling of different aspects of processes is desirable. For knowledge-intensive processes, we outline how to combine process models for structured routine aspects with the ad-hoc activities and flexibility of social software in the same context. Therefore, a case comprises modeled subprocesses as well as ad-hoc activities and artifacts. The shared context allows to transparently combine aspects and deviate from predefined models. We prototypically implement our approach and show that ad-hoc project management and different notations can be applied within the same case.<br
CRIS-Team Scopus Importer:2021-11-26
Keywords: adaptive case management; subprocess modeling; knowledge-intensive business process; process flexibility